Design and fabricate gas stove stand and extractor hood stand - Muhammad Fadhli, Othman (2012)
This final year project is about to design and fabricate the gas stove stand with extractor hood rack that suit to be used in kitchen. The objective of the project is to design and fabricate gas stove stand with extractor hood rack. This project also describes the review of products which are available in the market following to the title of the project. Design generation is showed and solid three dimensional structure modelling of the gas stove stand and extractor hood stand design was developed with solid work software. This report also explain the fabrication process that carrying in this project. Descriptions of material also show on this report in order to design this project. As the conclusion, this project has achieved its goal through the succesful product making.